(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
Drug abuse among adolescents is a serious problem that requires an effective social rehabilitation approach in line with the goal of rehabilitation, which is to improve social functioning. In an effort to increase the effectiveness of social rehabilitation, researchers have integrated technology into interventions to help adolescent victims of drug abuse. This research examines rehabilitation interventions and the application of information technology to improve social functioning at the "Satria" Center in Baturraden. In this study, a qualitative approach was used in the form of interviews, observation, and documentation. This research introduces an innovative intervention and the application of information technology in improving social functioning, one of which is a public service called SABA PIE (Information and Education Center) Drugs. This service helps the resident identification process and facilitates appropriate interventions, SABA PIE provides education and raises awareness of the dangers of narcotics. The results of this study provide insight into the role of technology in improving the social functioning of adolescent victims of drug abuse. This article contributes to the development of knowledge about counseling and social rehabilitation, particularly in overcoming drug abuse among adolescents. It is hoped that these findings will help overcome the problem of drug abuse and improve the quality of life of adolescent victims of drug abuse.